Die leksikografiese hantering van woordgroepstamme - Gouws, R.H. (Lexikos, 1991)
The Lexicographical Treatment of Word Group Stems The lexicon of Afrikaans consists of a variety of lexical items which have to be included in Afrikaans dictionaries as lexical, sublexical and multilexical lemmas. This paper deals with the treatment of sublexical lemmas and focusses on one specific type of sublexical item, i.e. the stems of complex lexical items that have an alternative occurrence beyond the limitations of the complex, where this occurrence is not that of a word but rather of a word group. Afrikaans dictionaries have not yet given proof of the fact that the treatment of this type of lemma also falls within their scope. Attention is drawn to existing limitations impeding the inclusion of these stems as lemmas. It is shown that although these stems seldom have a semantic plus value that would oblige the lexicographer to include them as lemmas, their potential inclusion can be motivated on linguistic and metalexicographical principles. Utilizing the existing criteria for the inclusion of sublexical lemmas, a number of arguments are given to prove that these word group stems should be regarded as lexical items and therefore as potential lemmas. However, the current Afrikaans lexicographical endeavour, dominated by a word-based approach, does not make provision for these stems to be treated as multiword sublexical lemmas. Adhering to some existing policies regarding the selection and macrostructural occurrence of sublexical lemmas, a number of proposals are made to ensure a linguistically sound lexicographical treatment of word group stems. Although the proposals made in this paper are motivated from a theoretical perspective, they are primarily aimed at the enhancement of the Afrikaans lexicographical practice. However, the implications of this discussion are not only relevant to lexicographers but also to theoretical linguists. The paper offers a new look at the diversity of lexical items and the structure of the lexicon of Afrikaans. This emphasizes once again the importance of an interaction between theoretical linguistics and lexicography. Such an interaction will always prove to be beneficial to both linguist and lexicographer.